Função quadrática contexto e aplicações no cotidiano - ANDRÉ, Pedro Júnior dos Santos (2019)
The present work begins with a brief history about function, giving prominence to some mathematicians who had fundamental importance for its development. It also makes an approach to the concepts of function, concepts that were fundamental for the construction of this work. Later on, the evolution of quadratic function was discussed, speaking of mathematicians and their respective importance for the development of quadratic function throughout history. Entering the quadratic function subject were the definitions, graphs, canonical form, zeros of the quadratic function, maximum of the function and minimum, the vertex of the parabola, the image, and the axis of symmetry, and finally the applications of the quadratic function in several everyday situations.